Behind Bars. (January 2015) - Trestman, Robert L.; Ferguson, Warren; Dickert, Jeff
<x xml:space="preserve">Abstract</x> Academic health centers (AHCs), particularly those that are publicly funded institutions, have as their mission the treatment of disadvantaged populations, the training of the next generation of clinicians, and the development and dissemination of new knowledge to reduce the burden of disease and improve the health of individuals and populations. Incarcerated populations have the most prevalent and acute disease burden and health disparities in the United States, even in comparison with inner-city populations. Yet, only a small proportion of AHCs have reached out to incarcerated populations to fulfill their mission. Those AHCs that have partnered with correctional facilities have overcome concerns about the value and popularity of "training behind bars"; the cost, liability, and pragmatics of caring for a medically complicated population; and the viability of correctional health research and extramural research funding. They have done so to great benefit to patients, students, and faculty. Partnering with correctional facilities to provide health care offers opportunities for AHCs to fulfill their core missions of clinical service, education, and research, while also enhancing their financial stability, to the benefit of all. In this Commentary, the authors discuss, based on their experiences, these concerns, how existing partnerships have overcome them, and the benefits of such relationships to both AHCs and correctional facilities.